Influence of Mn on the iron-based friction material directly prepared by in situ carbothermic reaction from vanadium-bearing titanomagnetite concentrates. Issue 64 (29th October 2018) - Shui, Yue; Feng, Keqin; Zhang, Yanyan; Yan, Zidi
Abstract : In this work, we prepared an iron-based frictional material from vanadium-bearing titanomagnetite concentrates by in situ carbothermic reaction with improved tribological properties. Abstract : In this work, we prepared an iron-based frictional material from vanadium-bearing titanomagnetite concentrates by in situ carbothermic reaction with improved tribological properties. Effects of Mn content (1–4 wt%) on the microstructure and properties of iron-based friction material were investigated. The microstructure and properties of iron-based friction material with Mn are significantly improved. In particular, the friction coefficient decreases from 0.54 to 0.40–0.49 and the wear rate reduces from 1.899 × 10 −7 cm 3 J −1 to 0.229 × 10 −7 cm 3 J −1 – 1.309 × 10 −7 cm 3 J −1 . Appropriate Mn addition (1–3 wt%) contributes efficiently to the sintering densification and increasing laminated pearlites. Comparatively, the density, hardness and wear resistance are improved. The dominant wear mechanism changes from severe abrasive wear to mild abrasive wear and oxidative wear is also enhanced. However, when Mn content increases to 4 wt%, the microstructure, relative density, hardness and wear performance of iron-based friction material are deteriorated. Consequently, the optimal addition of Mn is 3 wt% in the iron-based friction material.